Analysis of individual micro-entrepreneur vision from the perspective of financial management - de Amorim Braga, Fabrício Jose; de Souza Silvestre, Fabiano; Oliveira, Ualison Rébula (Brazilian Journal of Operations & Production Management, 2018)
In the business world, the management of an organization calls for the development of information to support decisions. However, this is not a reality for a significant part of micro and small enterprises in Brazil, as several studies have shown. On this theme, with a focus on individual micro-entrepreneurs, the present study investigated how these businesspeople manage their finances and development. Methodologically, the study was supported by field research with 21 entrepreneurs in different business segments from the city of Volta Redonda (Rio de Janeiro state). Results indicated that 19% of respondents do not control cash flow and 76% do not analyze their financial results. Of those that use some kind of control, 67% monitor their finances by handwritten notes in notebooks. Regarding the sales forecast, less than half of the surveyed people do this type of control. Therefore, the surveyed micro-entrepreneurs need to develop financial and accounting management systems, focusing on a better financial control of their businesses. Although not conclusive, we believe the results obtained are related to the respondents’ low level of education.